Family Caregivers' Experiences of Caring for Patients With Heart Failure: A Descriptive, Exploratory Qualitative Study. Issue 2 (June 2015) - Etemadifar, Shahram; Bahrami, Masoud; Shahriari, Mohsen; Farsani, Alireza Khosravi
ABSTRACT: Background: Living with heart failure is a complex situation for family caregivers. Many studies addressing the challenges faced by heart failure family caregivers have already been conducted in Western societal settings. Sociocultural factors and perspectives influence the family caring experience and roles. The ethnic/culturally based differences in family caring behavior make this a subject worth further exploration and clarification. Purpose: This study explores the experiences of family caregivers in Iran of caring for patients with heart failure. Methods: A descriptive, exploratory, and qualitative approach was applied to gain authentic insight into the experiences of participants. Purposive sampling was used to recruit 21 family caregivers from three educational hospitals in Isfahan, Iran. Data were collected using semistructured interviews and field notes. Interviews and field notes were transcribed verbatim and concurrently analyzed. Results: Three major themes emerged from the analysis of the transcripts: caregiver uncertainty, lack of familial and organizational support, and Allah-centered caring. Participants believed that they did not have the basic knowledge related to their disease and drugs. In addition, they received little guidance from the healthcare team. Lack of support and insurance as well as financial issues were major problems faced by the caregivers. They accepted the providence of Allah and noted that Allah always helps them accomplish their caregiving responsibilities. Conclusions/Implications for Practice: The care performed by the caregivers of patients with heart failure exceeds their individual capabilities. Nurses, other healthcare providers, and health policy makers may use the findings of this study to develop more effective programs to address these challenges and to provide more effective support. Sociocultural factors and perspectives were the primary factors affecting the caregiving experiences of participants in this study. Improved understanding of these factors and perspectives will help healthcare providers develop and implement suitable intervention programs for caregivers. Healthcare professionals should develop context-based intervention programs to promote caregiver capabilities and encourage caregivers to participate to facilitate the caregiving roles of caregivers.